Office versus Ambulatory Blood Pressure: Can We Afford New Shoes? - Rizzo, Toni (MD Conference Express, 2012)
Brachial blood pressure (BP) measured using oscillometric devices correlates with disease endpoints such as myocardial infarction and stroke. Arterial stiffness may represent an easy surrogate marker for atherosclerotic burden using validated measurements such as pulse wave velocity and pulse wave analysis. This article discusses the relationship between office BP and ambulatory BP monitoring and the correlation of both BP measures with surrogate markers of disease.